The role of microRNAs in the pre-implantation mammalian embryo - Makri, K.D. (2021)
MicroRNAs (miRNAs) are small non-coding RNA molecules that exert regulatory actions in gene expression acting mainly via RNA silencing and post-transcriptional changes. Their actions are involved in important cell processes such as stress signalling, cell cycle progression, differentiation, and cell death. Mammalian gametes and pre-implantation embryos selectively express miRNAs that control oocyte maturation, spermatogenesis, fertilisation, embryonic division and growth, development and differentiation, and implantation.